2014
DOI: 10.1152/ajpheart.00465.2013
|View full text |Cite
|
Sign up to set email alerts
|

Mouse strain differences in metabolic fluxes and function of ex vivo working hearts

Abstract: In mice, genetic background is known to influence various parameters, including cardiac function. Its impact on cardiac energy substrate metabolism-a factor known to be closely related to function and contributes to disease development-is, however, unclear. This was examined in this study. In commonly used control mouse substrains SJL/JCrNTac, 129S6/SvEvTac, C57Bl/6J, and C57Bl/6NCrl, we assessed the functional and metabolic phenotypes of 3-mo-old working mouse hearts perfused ex vivo with physiological concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…However, a recent study reported that the cardiac output of C57BL/6N male mice is higher than that of their C57BL/6J counterparts. 5 Likewise, the effects of transverse aortic constriction on survival and the remodeling of left ventricles (LV) are much greater in C57BL/6N than in C57BL/6J mice. 6 Thus, evidence indicates that genetic drift can significantly alter cardiac phenotypes in the established C57BL/6 inbred strain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study reported that the cardiac output of C57BL/6N male mice is higher than that of their C57BL/6J counterparts. 5 Likewise, the effects of transverse aortic constriction on survival and the remodeling of left ventricles (LV) are much greater in C57BL/6N than in C57BL/6J mice. 6 Thus, evidence indicates that genetic drift can significantly alter cardiac phenotypes in the established C57BL/6 inbred strain.…”
mentioning
confidence: 99%
“…All computations were done with the R/Maanova package v.1.16.0. 5 For Real-Time quantitative PCR (RT-qPCR), samples containing 250-500ng of total RNA were reverse-transcribed (RT) using 200U of Superscript II reverse transcriptase (InVitrogen), as per the manufacturer's protocol. For samples containing smaller amounts of RNA, cDNA was generated from 10 ng of total RNA using the QuanTitect® reverse transcription kit (Qiagen).…”
mentioning
confidence: 99%
“…Furthermore, when 129S6 are fed a high-fat diet, gene expression of acylCoA oxidase 1 (Acox1) is reduced, a protein which traffics fatty acids towards β-oxidation, however, under the same dietary conditions in BALB/C mice there is no change in expression [56]. Interestingly, in an ex vivo working heart model, C57BL/6 mice had increased Acox1 expression as compared to 129/SvEvTac mouse heart, and as a result had decreased incorporation of oleic acid into TAG pools and more was utilized for β-oxidation than in 129/SvEvTac mouse heart [14]. Collectively, these studies demonstrate that observations in one mouse strain are not directly applicable to another strain, and support our supposition that for lipid metabolism, observations between mouse strains are not interchangeable.…”
Section: Discussionmentioning
confidence: 99%
“…Appreciating differences in characteristics between mouse strains to leverage the advantages and minimize potential pitfalls is an important consideration in experimental design [34]. For instance, C57BL/6 mice are commonly utilized in a substantial share of the scientific literature and are often used to study lipid metabolism, including studies on the efficacy of n-3 fatty acids on inflammation and injury [11,12,14,35,36]. On the other hand, SW mice are have been used in the pharmacology of fatty acid metabolism such as effects of pyridine exposure and highfat diets on lipid metabolism [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation